Introduction to research using subject indexes from Wilson. (H.W. Wilson, 1991)
Subject indexes are the most effective ways of locating precise, current and authoritative sources. This program shows the modern tools of information gathering, especially periodicals indexes in CD-ROMS of Wilson.